Exploring the longitudinal relationships between the use of grammar in text messaging and performance on grammatical tasks. (13th June 2014) - Wood, Clare; Kemp, Nenagh; Waldron, Sam
<x xml:space="preserve">Abstract</x> Research has demonstrated that use of texting slang (textisms) when text messaging does not appear to impact negatively on children's literacy outcomes and may even benefit children's spelling attainment. However, less attention has been paid to the impact of text messaging on the development of children's and young people's understanding of grammar. This study therefore examined the interrelationships between children's and young adults' tendency to make grammatical violations when texting and their performance on formal assessments of spoken and written grammatical understanding, orthographic processing and spelling ability over the course of 1 year. Zero‐order correlations showed patterns consistent with previous research on textism use and spelling, and there was no evidence of any negative associations between the development of the children's performance on the grammar tasks and their use of grammatical violations when texting. Adults' tendency to use ungrammatical word forms ('does you') was positively related to performance on the test of written grammar. Grammatical violations were found to be positively associated with growth in spelling for secondary school children. However, not all forms of violation were observed to be consistently used in samples of text messages taken 12 months apart or were characteristic of typical text messages. The need to differentiate between genuine errors and deliberate violation of rules is discussed, as are the educational implications of these findings.